GENETIC MODIFICATION FOR SALT AND DROUGHT TOLERANCE IN PLANTS THROUGH SODERF3 - Ali, M; Rafique, F; Ali, Q; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
Plants constitute the major part of the ecosystem and maintain balance through their different roles in the stability of the environment. As plants have an impact over environment; in the same manner environment interacts with plants. These interactions bring some productive results or sometimes may cause serious issues to plants. The environment poses some serious threats to plants as it is changing drastically over the course of years. Plants have been resistant to many of biotic and abiotic stresses naturally but now it is getting challenging. The major issues faced by plants are drought, high salt concentration, temperature and many other factors. These issues can be compensated by engineering plants with such novel genes which cause the release of ethylene responsive factor in the case of drought and salt intolerance. There are various studies to engineer the stress sensitive plants with SodERF3, a novel sugarcane ethylene responsive factor which causes promising tolerance in transgenic plants.